Türk Dili Nereden Nereye - Pala, İskender (İstanbul Kültür Üniversitesi Yayınları, 2002)
Türk dilinin Anadolu'daki gelişimi ve günümüzde kullanılan Türkçe'ye dönüşümü, değişik aşamalarda gerçekleşmiştir. Osmanlı Devleti 'nin imparatorluk çehresi kazandığı Fatih döneminden itibaren Cumhuriyet 'e geçiş ve modernleşme sürecinde Türk dilinin geçirdiği evreler dikkatle incelendiğinde, günümüzdeki dil bilincinin oluşması ve değişim aşamalarının doğru değerlendirilmesi bir gereklilik olur. Tarih boyunca dile önem veren Türk büyüklerinin tanınması da ayrıca önemlidir. Bu yazıda Türkçe'nin tarih içindeki gelişim süreci ana hatlarıyla verilmeye çalışılmıştır. The development of the Turkish language in Anatolia and its transition to modern Turkish has been realized in different stages. When one examines the phases that the Turkish language has undergone during the period of modernization and its transition to a Republic State starting with Fatih's era in which the Ottoman State acquired the status of an empire, one sees that it is necessary to create a conscious awareness for (the roots of) today's language so as to evaluate the phases of change appropriately. It is also important to acknowledge (learn about) the great Turkish figures who have attached importance to language throughout history. This essay is an attempt to outline (to trace) the historical development of the Turkish language.
Keywords: Turkish; Türkçe; History; Tarih; Change in Language; Dilde Değişim; Language Reform; Dil Devrimi